Tracing the Path of Islamic Political Movements in Indonesia - Istadiyantha Wardji (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2019)
Middle East is a religious Centrum for Muslims around the world, including the Indonesians. The relationship between Islam and the Middle East involves a complex political and historical process. The struggle for authentic Islam in the face of imperialist domination values and westernization of course the main reason for the spread of Islamic political movements to various parts of Asia.. The goal of this research is to discover the relationship between the Islamic political movements in the Middle East and the movements that have developed in Indonesia. There are numerous aspects which need to be understood about the emergence of Islamic political movements. The transmission of Islamic political movements to Indonesia has seen rapid developments since the 1970s and 1980s. The development of Islamic political movements began to gain momentum with the increase in the number of Indonesian students, of both school and university age, who went to study in the Middle East, which caused the relations between Indonesia and the Middle East to become closer on many levels. In the 1980s, Indonesian students in Saudi Arabia, Egypt, and other Middle Eastern countries absorbed many ideas related to political Islam or the movement of Islamic fundamentalism from the Middle East.